Recursively querying monitoring data in NFV environments - Xuejun Cai; John, Wolfgang; Meirosu, Catalin (2016 IEEE NetSoft Conference and Workshops (NetSoft), 2016)
In Network Function Virtualization (NFV), a network service is created by combining interconnected virtual network functions (VNF), which may include nested VNFs or end points. Querying the performance of a high-level, abstract network service is challenging due to the recursivity of the NFV architecture and the elasticity and dynamicity provided by the NFV infrastructure, typically realized by Cloud virtualization technologies. In this paper, we propose to use Datalog, a declarative logic programming language, to build a query engine which can provide recursive query capabilities on performance metrics of network services. We present the language and describe some example use cases for both compute and network metrics. We describe the design of a query engine utilizing the language, based on which we implemented a proof of concept system. The resulting experimental system has shown the effectiveness of the query language to recursively retrieve monitoring results of NFV environments.